A new designed linear Fresnel lens solar concentrator based on spectral splitting for passive cooling of solar cells. (15th February 2021) - Kiyaee, Soroush; Saboohi, Yadollah; Moshfegh, Alireza Z.
Graphical abstract: Highlights: A new design of a Fresnel lens based on spectral splitting. Passive cooling of a solar cell through diffracting the undesired spectrum portion. Optical-thermal simulation of the concentrator system. A temperature-dependent model by considering conduction, convection, and radiation. Comparison of different lenses in temperature and electrical efficiency of the cell. Abstract: The use of solar concentrators can be an alternative for initial cost reduction in the PV systems. However, they suffer from high cell temperature that can be overcome by different active or passive cooling approaches. Spectral splitting and the elimination of high-energy solar photons are effective solutions for cell temperature reduction. In this study, we developed a Polymethyl methacrylate Spectral Splitting Fresnel Lens (SSFL) for linear concentration using a new design, which directs the desired portion of the spectrum towards the cell and diffracts the rest to eliminate the use of beam splitters or nanofluids in the spectral splitting system. Different SSFLs were considered for directing the spectral ranges from 400 to 1150 nm to 800–1150 nm onto the silicon solar cell under a 10x concentration ratio. For this purpose, optical and heat transfer models were developed through simulation in the Comsol Multiphysics software and validated using available experimental dada in literature. Regarding the assumed parameters, the SSFL with 600–1150 nm spectral range with an optical efficiency of 81% was selected as the optimal lens that not only increases the weighted energy output by 14% but also reduces the cell temperature by 48 °C compared to the lens with 400–1150 nm spectral range. Indeed, no active or passive coolant is used in this system and no cost is imposed on the system. The cost-free property of this method in the FL-based CPV systems makes it an economical option for industrial production.